Association of microbe with different size of soil particle size fraction / Mohd Azizy Azizan - Azizan, Mohd Azizy (Faculty of Plantation and Agrotechnology, 2019)
Soil particles vary greatly in size, and soil scientists classify soil particles into sand, silt, and clay. Starting with the finest, clay particles are smaller than 0.002 mm in diameter. Some clay particles are so small that ordinary microscopes do not show them. Silt particles are from 0.002 to 0.05 mm in diameter. Sand ranges from 0.05 to 2.0 mm. Particles larger than 2.0 mm are called gravel or stones. Most soils contain a mixture of sand, silt and clay in different proportions. Soil structure depends on the association between mineral soil particle (sand, silt, and clay) and organic matter, in which aggregates of different size and stability are formed. Due to differences in mineralogical composition and organic matter density, soil particle size fractions (PSF) provide different surface properties and micro-environments, which may affect the adsorption of chemicals and select for distinct microbial community. In this experiment, two methods are used which are sieving and spread plate method. Sieving process is important to get the different size of soil particle. Meanwhile, spread plate method is used to determine the quantity of microbe in every different size of soil particle. Therefore, the result will determine which size of soil particle(silt, sand, clay) have the most microbial activity.